Expecting better : why the conventional pregnancy wisdom is wrong--and what you really need to know - Oster, Emily (Oster, Emily ParentData series, 2024)
When award-winning economist Emily Oster was a mom-to-be herself, she evaluated the data behind the accepted rules of pregnancy, and discovered that most are often misguided and some are just flat-out wrong. Debunking myths and explaining everything from the real effects of caffeine to the surprising dangers of gardening, Expecting Better is the book for every pregnant woman who wants to enjoy a healthy and relaxed pregnancy--and the occasional glass of wine.